2006
DOI: 10.1038/sj.gene.6364355
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel G245R polymorphism in the IL-2 receptor β membrane proximal domain associated with human visceral leishmaniasis

Abstract: Binding of the interleukin-2 (IL-2) to the IL-2 receptor (IL-2R) triggers a series of intracellular events culminating in lymphocyte proliferation and differentiation. We report here the identification of a novel G245R polymorphism in the membrane proximal domain of the IL-2 receptor b chain (IL-2Rb). Present at a frequency of 7.2%, the IL-2-Rb G245R was identified in a population of Eastern Sudan exposed to a severe outbreak of visceral leishmaniasis (VL), a disease associated with a marked depression of T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…We previously identified variants of the IL2RB gene predisposing individuals infected with L. donovani to KA (14). This prompted us to evaluate the expression profiles of the genes of the IL-2 pathway in Leishmania-infected tissue.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously identified variants of the IL2RB gene predisposing individuals infected with L. donovani to KA (14). This prompted us to evaluate the expression profiles of the genes of the IL-2 pathway in Leishmania-infected tissue.…”
Section: Resultsmentioning
confidence: 99%
“…However, the SNP associated with KA in Sudan (14) was not associated with CL in Brazilians. Further studies are therefore required to determine whether disease dissimilarities and/or different linkage disequilibrium structures between these two populations could account for such results.…”
Section: Foxp3mentioning
confidence: 95%
See 2 more Smart Citations
“…We would then expect that deficiencies in IL-2 signaling pathways would have an impact on the outcome of the response. Interestingly, human genetic studies revealed an association of functional polymorphisms in the b-chain CD122 with visceral Leishmaniasis triggered by Leishmania donovani (60). Further work will be needed to demonstrate such a link.…”
Section: Discussionmentioning
confidence: 99%